2017
DOI: 10.1371/journal.pone.0170316
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Otitis Media with Spontaneous Perforation of the Tympanic Membrane in Young Children and Association with Bacterial Nasopharyngeal Carriage, Recurrences and Pneumococcal Vaccination in Catalonia, Spain - The Prospective HERMES Study

Abstract: The Epidemiology of otitis media with spontaneous perforation of the tympanic membrane and associated nasopharyngeal carriage of bacterial otopathogens was analysed in a county in Catalonia (Spain) with pneumococcal conjugate vaccines (PCVs) not included in the immunization programme at study time. A prospective, multicentre study was performed in 10 primary care centres and 2 hospitals (June 2011-June 2014), including all otherwise healthy children ≥2 months ≤8 years with otitis media presenting spontaneous t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 48 publications
1
25
0
2
Order By: Relevance
“…The validity of evaluation of progression via OM incidence per carrier is suggested by meta-analytic findings of high (Ͼ80%) concordance in S. pneumoniae and NTHi detection from nasopharyngeal and MEF cultures in severe OM cases (51), such as those necessitating MEF culture in our study. Nonetheless, molecular diagnostic tools may offer enhanced sensitivity in comparison to culture as performed here (52)(53)(54). Such methods may be particularly important for estimating progression rates of serotypes that are rarely detected in carriage or disease: despite the large sample population used in our study, odds ratio estimates were sensitive to the lack of detection of episodes of either carriage (e.g., serotypes 5, 7B, 7F, 8, 15B/C, 24F, and 33F) or disease (serotypes 19B and 22F) in both single-species and mixed-species contexts.…”
Section: Discussionmentioning
confidence: 99%
“…The validity of evaluation of progression via OM incidence per carrier is suggested by meta-analytic findings of high (Ͼ80%) concordance in S. pneumoniae and NTHi detection from nasopharyngeal and MEF cultures in severe OM cases (51), such as those necessitating MEF culture in our study. Nonetheless, molecular diagnostic tools may offer enhanced sensitivity in comparison to culture as performed here (52)(53)(54). Such methods may be particularly important for estimating progression rates of serotypes that are rarely detected in carriage or disease: despite the large sample population used in our study, odds ratio estimates were sensitive to the lack of detection of episodes of either carriage (e.g., serotypes 5, 7B, 7F, 8, 15B/C, 24F, and 33F) or disease (serotypes 19B and 22F) in both single-species and mixed-species contexts.…”
Section: Discussionmentioning
confidence: 99%
“…The validity of evaluating progression via OM incidence per carrier is suggested by meta-analytic findings of high concordance (>80%) in Spn and NTHi detection from nasopharyngeal and MEF cultures in severe OM cases (51), such as those necessitating MEF culture in our study. Nonetheless, molecular diagnostic tools may offer enhanced sensitivity in comparison to culture as performed here (52)(53)(54). Such methods may be particularly important for estimating progression rates of serotypes that are rarely detected in carriage or disease: despite the large sample in our study, odds ratio estimates were sensitive to the lack of detection of episodes of either carriage (e.g., serotypes 5, 7B, 7F, 8, 15B/C, 24F, 33F) or disease (serotypes 19B, 22F) in either single-or mixed-species contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Although NTHi is a known cause of respiratory infections, such as otitis media and pneumonia, [1][2][3] its potential to cause a nosocomial URI outbreak is not fully understood. Andersson et al 20 reported an outbreak of NTHi that occurred in a longterm care facility for the elderly in Sweden.…”
Section: Discussionmentioning
confidence: 99%